Implementasi Game RPG Sebagai Media Edukasi Keterampilan Kewirausahaan Berbasis Mobile - Teguh Setiadi; Febriyanti Darnis (Jurnal Teknologi Informasi dan Terapan, 2023)
Training in the field of entrepreneurship can be enhanced by using developmental games to educate students. Simulation models for entrepreneurial strategies can be developed through RPG games. The GBL (Game based learning) implementation model was used in this study to provide training for entrepreneurial practice by implementing RPG games. Entrepreneurial practices developed by preparing businesses, investing for businesses in the form of goods, main capital in businesses, determining the prices of products sold, conducting buying and selling transactions, and managing all business needs are used in conducting research using the Development or R&D method. to create a multimedia that is interactive, resulting in an interactive mobile learning experience. The application of role-playing games received a score of "very good" in the entrepreneurship park at Harapan Mulya Vocational School, indicating that it was possible to provide vocational students with teachers who could provide them with information about how to become an entrepreneur.